Updated clinical and biological information from the two-stage phase II study of imatinib mesylate in subjects with relapsed/refractory neuroblastoma. (2nd September 2018) - Morandi, Fabio; Amoroso, Loredana; Dondero, Alessandra; Castriconi, Roberta; Parodi, Stefano; Luksch, Roberto; Casale, Fiorina; Castellano, Aurora; Garaventa, Alberto; Moretta, Alessandro; Bottino, Cristina; Ponzoni, Mirco; et al.
ABSTRACT: Several studies support the notion that the kinase inhibitor Imatinib mesylate exerts off-target effects on cells of the immune system. After our first report of continuous daily oral administration in subjects with relapsed/refractory neuroblastoma (NB, EudraCT: 2005–005778-63), here we update the clinical information and report additional information on potential surrogate markers for prediction of efficacy. Peripheral blood (PB) samples collected at study entry and after the first and second cycle of Imatinib mesylate treatment were tested for IFN- γ, TNF-α, TGF-β, IL-10, CXCL12 and soluble (s) B7-H6 plasma levels. In addition, paired PB and bone marrow (BM) samples collected at study entry and after the second Imatinib cycle were evaluated for CXCL12, CXCR4 and NKp30 isoform mRNA levels. Correlation between each parameter level and response/outcome was then evaluated. Out of the six subjects still alive at the time of the first report, thee died after additional therapy, two for NB progression and one for a second malignancy. Three are presently alive and cured from NB at 10 years after the first Imatinib cycle. Of these, one achieved complete response (CR) during Imatinib treatment and never relapsed, one had a local relapse removed by surgery and the third received TVD as rescue therapy. Response and outcome were associated with low Imatinib exposure, whereas none of the tested immunological and molecular parameters was predictive of response/outcome. However, after Imatinib treatment NKp30 isoform mRNA levels significantly increase in BM samples, indicating that Imatinib mesylate exerted an off-target effect on NK cells in vivo . Imatinib mesylate efficacy in relapsed/refractory NB has been confirmed at a longer follow-up, supporting its inclusion in new Phase II trials for these subjects, that should envisage collection of samples to evaluate the predictive power of other potential surrogate markers of efficacy.